FACTORS INFLUENCING ON SATISFACTION OF SIRIRAJBIMUKSTHANACTORS’s VISITORS - Kuntika Viboonpin กุลทิกา วิบูลย์ปิ่น; Prasopchai Pasunon ประสพชัย พสุนนท์ (Dusit Thani College Journal, 2018)
This research aimed to study personal factors and marketing mix factors influencing on satisfaction of Siriraj Bimuksthan Museum ’ s visitors and to study the level of satisfaction of Siriraj Bimuksthan Museum ’ s visitors. By the quantitative research, data were collected by the questionnaire from a sample of 385 visitors. For data analysis, descriptive statistics including parsing frequency, percentage, mean and standard deviation was used. And inference statistics for testing hypotheses, the regression analysis was utilized. The results of information concerning the personal factor of visitors indicated that most visitors were female, aged between 46-55 years of undergraduate study, government/state enterprise employees, and having revenue more than 25,000 baht. Pertaining the marketing mix factors, it was found that overall visitors focused on the factors of the marketing mix for services at a high level ( ) with the most concern on the physical environment ( ), followed by technical museum exhibits ( ), quality of service ( ), ability to create knowledge ( ), and the least is technical PR ( ).On the satisfaction of the visitors it was found that, overall was high ( ) over expectation ), followed by the service valued for money ) and the lowest is a better museum than the others ( ).The test hypothesis showed that personal factors did not affect the satisfaction of visitors at the significant level of 0.05 and the marketing mix affected on the satisfaction of visitors at the significant level of 0.05.